The international flavours of corporate social responsibility. (8th June 2009) - Peters, Richard; Vassar, John A.
This article discusses the cultural implications of corporate social responsibility (CSR) specifically as it relates to the Hofstede's dimensions of individualism and collectivism. We propose that not only can these values alter organisational orientations towards CSR but may ultimately affect firm strategic performance in foreign direct investment. Theoretical arguments and discussion are provided as well as the possible benefits to both academics and managers that can be procured from greater empirical investigation of this line of research.